2016
DOI: 10.1177/1750698016673237
|View full text |Cite
|
Sign up to set email alerts
|

Generational dynamics in Spain: Memory transmission of a turbulent past

Abstract: Despite the crucial transformations that Spain has experienced since Franco’s death, and in contrast with other countries that have democratized in recent decades, considerable reluctance remains toward implementing transitional justice measures. On the contrary, there is a tendency to hold on to a framework that combines the Amnesty Law of 1977 with partial reparations as the best guarantors of democratic stability. According to extant literature, generational change has played a fundamental role in the direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…In 2007, 30 years after the transition—after another generational turnover, so to say—the government under Zapatero passed the Law of Historical Memory (LHM) that conceded families the right to know of the whereabouts of their deceased family members and thus opened the legal way to exhumations, albeit without regular financial or institutional support. With regard to attitudes concerning the LHM, public surveys show clear generational differences among the populace, as Aguilar and Ramírez-Barat (2017) point out in this journal. Whereas the intermediate generation stated fears that digging up the past might provoke political violence and social division, the younger generations, those born after the transition, in tendency supported the law.…”
Section: The Spanish Transition Historical Memory and Intergenerational Relationsmentioning
confidence: 58%
See 2 more Smart Citations
“…In 2007, 30 years after the transition—after another generational turnover, so to say—the government under Zapatero passed the Law of Historical Memory (LHM) that conceded families the right to know of the whereabouts of their deceased family members and thus opened the legal way to exhumations, albeit without regular financial or institutional support. With regard to attitudes concerning the LHM, public surveys show clear generational differences among the populace, as Aguilar and Ramírez-Barat (2017) point out in this journal. Whereas the intermediate generation stated fears that digging up the past might provoke political violence and social division, the younger generations, those born after the transition, in tendency supported the law.…”
Section: The Spanish Transition Historical Memory and Intergenerational Relationsmentioning
confidence: 58%
“…Aguilar and Ramírez-Barat (2017) point to the fact that after 2011, with the land-slide victory of the right-wing Partido Popular (PP), these historical memories initiatives were completely excluded from government support, which abandoned the implementation of the LHM. This was usually justified precisely in the framework of austerity policies, that is, the need for budget cuts in reaction to the economic crisis.…”
Section: The Spanish Transition Historical Memory and Intergenerational Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of generational shifts in activism in societies in and after conflict sheds light on processes of continuation and change, in the vibrant processes of shaping collective memories. Other case studies have shown important angle of studying the generational shifts in activism in divided societies, especially as related to contested pasts (see, e.g., Aguilar & Ramirez-Barat, 2016;Massalha, Kaufman, & Levy, 2017; and last, as relates to the memory of Yugoslavia and the breakup of Yugoslavia, Plamberger, 2016). 13.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…93 Some of these different attitudes to the HML can be explained by the left/right division of the political spectrum, but they must also be understood in the context of generational differences. Most of those opposed to confront the past 'belong mainly to the second generation born after the Civil War', 94 and had grown up during the dictatorship. They were conditioned to silence, as discussed above in the context of the exhumations, impacted by 'their inherited inability to construct a verbal representation of what was happening to them and what had happened to their parents.'…”
mentioning
confidence: 99%